Emotional climate in residential care scale for youth: Psychometric properties and measurement invariance. (May 2023) - Santos, Laura; Martins, Joana; Ribeiro da Silva, Diana; Matos, Marcela; Pinheiro, Maria do Rosário; Rijo, Daniel
Highlights: Increased attention has been given to residential climate as a therapeutic tool. Emotional Climate in Residential Care Scale for youth (ECRC-Y) was validated. The ECRC-Y assess the emotional climate according to 3 affect regulation systems. Threat, drive and soothing emotions subscales showed good psychometric properties. Girls in residential care reported higher level of threat emotions than boys. Abstract: Research has shown that social and contextual factors, such as climate in Residential Youth Care (RYC), are key protective factors for better outcomes in youth who experienced maltreatment. Even if increasing attention has been given to residential climate as a therapeutic tool, available measures are still scarce and revealed some limitations. This study aims to adapt and validate a brief self-report measure to assess the emotional climate of residential care homes as perceived by youth who live there: the Emotional Climate in Residential Care Scale for youth (ECRC-Y). Participants were 372 youth (61.8% girls), aged between 12 and 24 years old, living in 33 Portuguese residential care facilities. The ECRC-Y was adapted from the Emotional Climate in the Classroom Scale, which is a 15-item measure based on an evolutionary approach, assessing the emotional climate according to three affect regulation systems: threat, drive, and soothing systems. A confirmatory factor analysis (CFA) was performed, and measurement invariance was tested for sex. The CFA indicated a trifactorial measurement model, in agreement with the theoretically proposed model. The ECRC-Y showed adequate internal consistency and construct validity in relation to external variables. Measurement invariance was supported for the ECRC-Y. Girls presented higher levels of threat related emotions, when compared with boys. Overall, the ECRC-Y is an appropriate self-report measure that may be useful for research and practice purposes within RYC settings, giving information about the emotional climate of residential care homes as perceived by youth in care.